2020
DOI: 10.6007/ijarbss/v10-i3/7052
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Non-Disclosure of Accountability Practices Information on the Website of Malaysian Local Governments

Abstract: This paper attempts to explore the reasons for non-disclosure of accountability practices information (API) on the website by selected Malaysian local governments. The behaviours of Malaysian local governments towards non-disclosure of API is explained from the perspective of institutional isomorphism concept. Data collection was carried out through semi structured interviews among officers who are directly or indirectly involved in making decision related to accountability practices and agenda. The analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 25 publications
0
8
0
4
Order By: Relevance
“…SC is a "process of monitoring and correcting a firm's strategy and performance" (Dess et al, 2017, p. 268) which is used in the strategy to achieve the intended goals, including disclosure practices. Two central aspects of SC predominantly used in the management field of study as suggested by Dess et al (2017) are BC and IC These two aspects of control have been found to significantly affect the non-disclosure practices of the organisation (Ahmad, Joseph, & Said, 2020). Along the same line, it is suggested that the DACP could be explained by analysing reasons for disclosure with isomorphism and SC concept i.e.…”
Section: Strategic Controlmentioning
confidence: 96%
See 2 more Smart Citations
“…SC is a "process of monitoring and correcting a firm's strategy and performance" (Dess et al, 2017, p. 268) which is used in the strategy to achieve the intended goals, including disclosure practices. Two central aspects of SC predominantly used in the management field of study as suggested by Dess et al (2017) are BC and IC These two aspects of control have been found to significantly affect the non-disclosure practices of the organisation (Ahmad, Joseph, & Said, 2020). Along the same line, it is suggested that the DACP could be explained by analysing reasons for disclosure with isomorphism and SC concept i.e.…”
Section: Strategic Controlmentioning
confidence: 96%
“…There are limited studies that link BC and disclosure practices, particularly DACP. Recent work by Ahmad et al (2020) investigated what causes non-disclosure of information and found that BC is one of the factors determining whether an organisation discloses information on websites or not. The BC system exists due to strong culture which includes knowledge, values, belief, and habits in organisations that create a system of informal rules that influences how the people inside the organisations behave (Anuja, 2021).…”
Section: Behavioural Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Outros estudos desenvolveram a questão dos determinantes do controle social dos recursos do fundo especial do ponto de vista da responsabilidade social dos municípios e das instituições envolvidas (Walker, 2016;Uygur, 2020;Ayliffe et al, 2017;Bahramirad, 2018) e transparência (Ahmad et al, 2020;Pivac et al, 2017;Abu Bakar & Saleh, 2015;Ortega-Rodríguez et al, 2020), além de envolver questões subjacentes e interligadas, como processos de doação para projetos (Trussel & Parsons, 2007;Yao, 2015;Degasperi & Mainardes, 2017), a prestação de contas das entidades sociais (Azevedo, 2017;Caldas & Freire, 2020;Moreno-Albarracín et al, 2020), a divulgação (Ling et al , 2018;Shahib & Risky, 2017;Nor et al, 2019;Agustiningsih et al, 2017), mídias sociais e ação comunicativa, que são importantes para entender as diferenças significativas que ocorrem no volume transmitido às instituições sociais.…”
Section: Referencia Teóricaunclassified
“…UNLaM Departamento de Ciencias Económicas -FR1 Otros estudios han desarrollado el tema sobre los determinantes del control social de los recursos del fondo especial desde el punto de vista de la responsabilidad social de los ayuntamientos y de las instituciones implicadas (Walker, 2016;Uygur, 2020;Ayliffe et al, 2017;Bahramirad, 2018) y de la transparencia (Ahmad et al, 2020;Pivac et al, 2017;Abu Bakar & Saleh, 2015;Ortega-Rodríguez et al, 2020), además de implicar temas subyacentes e interconectados, como los procesos de donación para proyectos sociales (Trussel & Parsons, 2007;Yao, 2015;Degasperi & Mainardes, 2017), la rendición de cuentas de las entidades sociales (Azevedo, 2017;Caldas & Freire, 2020;Moreno-Albarracín et al, 2020), la divulgación (Ling et al, 2018;Shahib & Risky, 2017;Nor et al, 2019;Agustiningsih et al, 2017), los medios sociales y la acción comunicativa, que son importantes para entender las diferencias significativas que se producen en el volumen transmitido a las instituciones sociales.…”
Section: Marco Teóricounclassified